Presence of novel compound BCR-ABL mutations in late chronic and advanced phase imatinib sensitive CML patients indicates their possible role in CML progression. Issue 4 (3rd April 2017) - Akram, Afia Muhammad; Iqbal, Zafar; Akhtar, Tanveer; Khalid, Ahmed Mukhtar; Sabar, Muhammad Farooq; Qazi, Mahmood Hussain; Aziz, Zeba; Sajid, Nadia; Aleem, Aamer; Rasool, Mahmood; Asif, Muhammad; Aloraibi, Saleh; et al.
ABSTRACT: BCR-ABL kinase domain (KD ) mutations are well known for causing resistance against tyrosine kinase inhibitors (TKIs) and disease progression in chronic myeloid leukemia (CML). In recent years, compound BCR-ABL mutations have emerged as a new threat to CML patients by causing higher degrees of resistance involving multiple TKIs, including ponatinib. However, there are limited reports about association of compound BCR-ABL mutations with disease progression in imatinib (IM) sensitive CML patients. Therefore, we investigated presence of ABL-KD mutations in chronic phase (n = 41), late chronic phase (n = 33) and accelerated phase (n = 16) imatinib responders. Direct sequencing analysis was used for this purpose. Eleven patients (12.22%) in late-CP CML were detected having total 24 types of point mutations, out of which 8 (72.72%) harbored compound mutated sites. SH2 contact site mutations were dominant in our study cohort, with E355G (3.33%) being the most prevalent. Five patients (45%) all having compound mutated sites, progressed to advanced phases of disease during follow up studies. Two novel silent mutations G208G and E292E/E were detected in combination with other mutants, indicating limited tolerance for BCR-ABL1 kinase domain for missense mutations. However, no patient in early CP of disease manifested mutated ABL-KD . Occurrence of mutations was found associated with elevated platelet count (p = 0.037) and patients of male sex (p = 0.049). The median overall survival and event free survival of CML patients (n = 90) was 6.98 and 5.8 y respectively. The compound missense mutations in BCR-ABL kinase domain responsible to elicit disease progression, drug resistance or disease relapse in CML, can be present in yet Imatinib sensitive patients. Disease progression observed here, emphasizes the need of ABL-KD mutation screening in late chronic phase CML patients for improved clinical management of disease.